Bisphosphonate-related osteonecrosis of jaw (BRONJ): an anti-angiogenic side-effect? - Petcu Eugen B; Ivanovski Saso; Wright Robert G; Slevin Mark; Miroiu Rodica I; Brinzaniuc Klara (BMC, 2012)
Abstract Bisphosphonates are recommended in the treatment of osteoporosis and some cancers, in which case they prevent the appearance of bone metastasis. The patients taking bisphosphonates are at increased risk of developing bisphosphonate-related osteonecrosis of jaw (BRONJ) which is characterised by the presence of an un-healing wound after dental surgery. BRONJ might represent an anti-angiogenic side effect. However, the real number of patients with BRONJ might be higher than currently recorded. Considering the differential diagnosis which includes various primary and secondary cancers, a correct histopathological diagnosis is very important. The morphological criteria for diagnosis of BRONJ are highlighted in this material. Virtual Slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1813972972323288